SINGLE-THREADING BASED DISTRIBUTED-MULTIPROCESSOR-MACHINES AFFECTING BY DISTRIBUTED-PARALLEL-COMPUTING TECHNOLOGY - ABDULQADER, DILDAR MASOOD; ZEEBAREE, SUBHI R. M.; ZEBARI, RIZGAR R.; SALEH, SAGVAN ALI; RASHID, ZRYAN NAJAT; SADEEQ, MOHAMMED A. M. (Journal of Duhok University, 2023)
The objective of this study is to propose a methodology for developing a distributed memory system with multiple computers and multicore processors. This system can be implemented on distributed-shared memory systems, utilizing the principles of client/server architecture. The presented system consists of two primary components: monitoring and managing programs executed on distributed-multi-core architectures with 2, 4, and 8 CPUs in order to accomplish a specific task. In the context of problem-solving, the network has the capacity to support multiple servers along with one client. During the implementation phase, it is imperative to consider three distinct scenarios that encompass the majority of design alternatives. The proposed system has the capability to compute the Total-Task-Time (TTT) on the client side, as well as the timings of all relevant servers, including Started, Elapsed, CPU, Kernel, User, Waiting, and Finish. When designing User Programs (UPs), the following creation scenario is carefully considered: The term "single-process-multi-thread" (SPMT) refers to a computing paradigm where a single process is executed by multiple threads The results unequivocally indicate that an augmentation in processing capacity corresponds to a proportional enhancement in the speed at which problems are solved. This pertains specifically to the quantity of servers and the number of processors allocated to each server. Consequently, the duration required to finish the assignment increased by a factor of 9.156, contingent upon three distinct scenarios involving SPMT UPs. The C# programming language is utilized for the coding process in the implementation of this system.